2010
DOI: 10.1159/000323829
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Coronary Artery Stenoses with Contrast-Enhanced Whole-Heart Coronary Magnetic Resonance Angiography at 3.0 T

Abstract: Purpose: To prospectively evaluate the accuracy of contrast-enhanced whole-heart coronary magnetic resonance angiography (CMRA) at 3.0 T, with the use of sublingual nitroglycerin and abdominal banding, for assessing significant stenosis (≧50% lumen diameter reduction) in patients with suspected coronary disease, using conventional coronary artery angiography as the reference standard. Methods: We prospectively studied 71 consecutive patients with suspected coronary artery disease scheduled for conventional cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…By comparison, our study analyzed the left main coronary artery and the proximal, middle, and distal segments of 3 main vessels, and came out with similar diagnostic performance with the sensitivity, specificity, positive and negative predictive values of 92.3%, 96.7%, 83.7%, and 98.6% in segment-based analysis, and 100.0%, 66.7%, 92.3%, and 100.0% in patient-based analysis. Compared with previous studies 40–43 that reported the sensitivity, specificity, PPV, and NPV of 73%, 95%, 50%, and 98% in segment-based analysis by gadobutrol-enhanced CMRA, 40 and 93%, 42%, 70%, and 81% in patient-based analysis by noncontrast-enhanced CMRA, 6 our results showed the best diagnostic performance regarding all the parameters.…”
Section: Discussioncontrasting
confidence: 62%
“…By comparison, our study analyzed the left main coronary artery and the proximal, middle, and distal segments of 3 main vessels, and came out with similar diagnostic performance with the sensitivity, specificity, positive and negative predictive values of 92.3%, 96.7%, 83.7%, and 98.6% in segment-based analysis, and 100.0%, 66.7%, 92.3%, and 100.0% in patient-based analysis. Compared with previous studies 40–43 that reported the sensitivity, specificity, PPV, and NPV of 73%, 95%, 50%, and 98% in segment-based analysis by gadobutrol-enhanced CMRA, 40 and 93%, 42%, 70%, and 81% in patient-based analysis by noncontrast-enhanced CMRA, 6 our results showed the best diagnostic performance regarding all the parameters.…”
Section: Discussioncontrasting
confidence: 62%
“…Yang et al [7] demonstrated the feasibility of accurate detection of significant stenosis in a singlecenter study. Initial experiments have shown that CE-CCMRA provides sufficiently high sensitivity and a negative predictive value to exclude significant stenosis in patients suspected of having CAD [29]. In addition, that study [29] suggested that image quality can be further improved by sublingual nitroglycerin and abdominal banding.…”
Section: Discussionmentioning
confidence: 99%
“…The publication years of these studies ranged from 2005 to 2022; 23 of these studies utilized 1.5 T MRI technology [ 13 25 , 28 , 30 , 31 , 33 37 , 44 46 ], while 11 utilized 3.0 T technology [ 26 , 27 , 29 , 32 , 38 43 , 45 ]. The countries of publication were diverse, with China having 11 reports [ 18 , 26 , 32 , 34 , 38 , 39 , 41 45 ], Germany having 8 reports [ 13 , 15 , 19 , 25 , 27 , 29 , 31 , 35 ], Japan having 7 reports [ 14 , 17 , 24 , 28 , 30 , 37 , 40 ], United Kingdom [ 21 , 46 ] having two reports and various other countries such as the United States [ 20 ], Korea [ 16 ], Switzerland [ 36 ], Portugal [ 33 ], Belgium [ 23 ], and Turkey [ 22 ] having one report each. In terms of study design, one study employed a prospective multicenter design [ 28 ], while 19 employed prospective single-center designs [ 13 15 , 17 , 21 , 23 , 25 27 , 29 32 , 37 39 , 43 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The countries of publication were diverse, with China having 11 reports [ 18 , 26 , 32 , 34 , 38 , 39 , 41 45 ], Germany having 8 reports [ 13 , 15 , 19 , 25 , 27 , 29 , 31 , 35 ], Japan having 7 reports [ 14 , 17 , 24 , 28 , 30 , 37 , 40 ], United Kingdom [ 21 , 46 ] having two reports and various other countries such as the United States [ 20 ], Korea [ 16 ], Switzerland [ 36 ], Portugal [ 33 ], Belgium [ 23 ], and Turkey [ 22 ] having one report each. In terms of study design, one study employed a prospective multicenter design [ 28 ], while 19 employed prospective single-center designs [ 13 15 , 17 , 21 , 23 , 25 27 , 29 32 , 37 39 , 43 46 ]. The remaining studies were retrospective in nature.…”
Section: Resultsmentioning
confidence: 99%